Cognitive Behavior Group Counseling with Cognitive Restructuring and Problem Solving Techniques to Reduce Anxiety (Universitas Negeri Semarang, 2019)
This study aimed to examine the effectiveness of cognitive behavior therapy group counseling with cognitive restructuring and problem-solving techniques to reduce the anxiety of the students of Akademi Kebidanan Abdi Husada Semarang. The study used an experimental method with the randomized pre-test – post-test comparison group. It involved 18 female students of AKBID Abdi Husada who had anxiety in the clinical clerkship. These 18 students were divided into three groups, namely the group of group counseling with cognitive restructuring technique, group counseling with problem-solving technique, and group counseling with the combination of cognitive restructuring and problem-solving techniques. The results showed that students who joined group counseling could reduce their anxiety. However, the reduction was more effective when using the combination of both cognitive restructuring and problem-solving techniques. These findings showed that group counseling with cognitive restructuring and problem-solving techniques is effective to reduce female students’ anxiety.